Content Analysis on Quick Services Information System (SILAT) at the Indonesia Ministry of Marine and Fisheries - Muhammad Reza Budiman; Rita Myrna; Enjat Munajat (Dinasti Publisher, 2023)
Indonesia's ocean area is 6.4 million km². With these wide waters, Indonesia is a maritime country and has great fishery potential to optimize its utilization. To optimize the potential of fishery resources, the central government through the Ministry of Marine Affairs and Fisheries (KKP) launched an electronic/online capture fishery business licensing service policy called the Quick Services Information System (SILAT). There are 10 regulations related to and supporting the SILAT policy, which consist of Laws, Government Regulations, Presidential Regulations, and Regulations of the Minister of Marine Affairs and Fisheries. The Indonesian government's regulations regarding the policy for the use of SILAT emphasize on the operational mechanism by making various methods, patterns, and procedures in the implementation of electronic licensing policies, especially SILAT. This finding suggests that the operational mechanism aspect is given higher priority in the implementation of SILAT so that the policy is expected to be successful and that the potential of fisheries resources is utilized to its fullest extent